Pengembangan Bahan Ajar Mata Pelajaran Dasar dan Pengukuran Listrik untuk Sekolah Menengah Kejuruan - Kusumam, Aliangga; Mukhidin, Mukhidin; Hasan, Bachtiar (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
This study is aimed to develop teaching materials of basic electrical and electrical measurement, and to find out the feasibility of the teaching materials that have been developed in SMK Negeri 1 Koba Bangka. This study used the method of Research and Development (R D) that begins with the preliminary study followed by the development phase and the product assessment. The subjects that consisted of three experts and 28 students of the Department of Electrical Installation Engineering were determined using purposive sampling technique. The data collection technique used documentation, interviews and questionnaires. The procedure of this study is the process of preparing the teaching materials through the following stages: (a) A preliminary study, by conducting interviews with the head of the program and the teachers. The analysis of the syllabus and core competencies. (b) Collecting learning resources and literature as well as the main points of the materials. (c) Preparing the draft of the materials. (d) The limited trial of the products (e) The extensive product testing. (f) The data analysis and evaluation. The results were the development of the teaching materials was based on the curriculum of 2013 and the syllabus of basic electrical and electrical measurement. The teaching materials were developed starting from the materials of electric current and electron current, electrical materials, passive elements, active elements, direct current resistive circuits, two poles theorem, power and efforts, switching circuits, the system of units of measurement, measuring instruments and electrical measurements, and the types of measuring devices.Penelitian ini bertujuan untuk mengembangkan bahan ajar dasar dan pengukuran listrik, dan mengetahui kelayakan bahan ajar yang telah dikembangkan menurut expert judgment dan peserta didik di SMKN I Koba Bangka. Metode penelitian ini menggunakan Research and Development (R D) yang diawali dengan studi pendahuluan dilanjutkan tahap pengembangan dan penilaian produk. Subjek penelitian ditentukan dengan menggunakan teknik purposive sampling yang terdiri dari tiga orang expert judgement dan 28 orang peserta didik teknik instalasi pemanfaatan tenaga listrik. Pengumpulan data dengan teknik studi dokumentasi, wawancara dan kuesioner berupa angket. Prosedur penelitian ini adalah proses penyusunan bahan ajar dasar dan pengukuran listrik melalui tahap-tahap sebagai berikut: (a) Studi pendahuluan, dengan melakukan wawancara terhadap ketua program dan guru. Studi analisis silabus dan menganalisa kompetensi dasar dalam penyusunan bahan ajar (b) Mengumpulkan sumber belajar dan literatur serta pokok-pokok materi yang akan disusun. (c) Penyusunan draft bahan ajar dasar dan pengukuran listrik. (d) Uji coba terbatas produk. (e) Uji coba lebih luas produk. (f) Pengolahan data dan evaluasi. Kesimpulan penelitian ini adalah pengembangan bahan ajar mata pelajaran dasar dan pengukuran listrik yaitu bahan dikembangkan dari kurikulum 2013 dan silabus mata pelajaran dasar dan pengukuran listrik. Materi bahan ajar dikembangkan mulai dari materi arus listrik dan arus elektron, bahanbahan listrik, elemen pasif, elemen aktif, rangkaian resistif arus searah, teorema dua kutub, daya dan usaha, peralihan rangkaian, sistem satuan pengukuran, alat ukur dan pengukuran listrik, dan jenis alat ukur.